Effect of climate on provincial-level banana yield in the Philippines - Arnold R. Salvacion (Information Processing in Agriculture, 2020)
This study assessed the effect of climate on banana yield in the Philippines using provincial level yield data and different climatic variables (i.e. annual rainfall, frequency of wet days, precipitation seasonality, annual mean temperature, temperature seasonality, and annual mean diurnal temperature range) derived from Climate Research Unit – Time Series (CRU-TS) dataset from year 1991–2016. First, trend analysis was applied to the time series of banana yield data for each province to determine presence of linear trend. Then, based on the result of linear trend analysis, multiple regression analysis was used to assess the effect on climate on provincial-level banana yield. Trend analysis showed that 71% of banana producing area in the country experience significant yield trend while multiple regression analysis showed that only 10% of the banana producing areas in the country is significantly affected by climate. Compared to rainfall, temperature variables, specifically temperature seasonality has the greater influence on provincial-level banana yield in the Philippines. Keywords: Banana, Climate, Yield trend, Philippines